Building an Understanding of Mathematics through Ethnic Mathematics: A Case Study of Learning in Bintuni Bay Regency - Ibrahim, Riza Andrian; W, Alim Jaizul (International Journal of Ethno-Sciences and Education Research, 2024)
This study explores the application of ethnomathematics in mathematics education within the context of Bintuni Bay Regency. Ethnomathematics is the approach of linking mathematical concepts with local cultural practices, aiming to make learning more relevant and engaging for students. The research focuses on how this approach enhances students' understanding and motivation by integrating elements of local culture, such as traditional textile patterns, food-sharing customs, and handicrafts, into the mathematics curriculum. A qualitative case study method was used, involving classroom observations, interviews with teachers and students, and document analysis across three primary schools in Bintuni Bay. The findings indicate that students responded positively to the ethnomathematical approach, showing increased engagement and improved comprehension of mathematical concepts when taught in a culturally relevant context. Teachers also observed higher levels of participation, although they faced challenges related to limited resources and inadequate training. Despite these obstacles, ethnomathematics proved to be a valuable tool for deepening students' critical thinking and creativity, as well as fostering a connection between academic learning and their cultural heritage. The study concludes that ethnomathematics has significant potential to improve the quality of mathematics education, especially in culturally diverse regions like Indonesia. However, to optimize its implementation, further support is needed, including teacher training and the development of culturally appropriate teaching materials. This research contributes to a growing body of literature advocating for the integration of local culture into the educational process, offering recommendations for policymakers and educators to develop more responsive and inclusive curricula